Enforcement Challenges in Human Rights Protection Under International Law - Nur 'Azah; Abd Rouf (Badan usaha Milik Desa Berkaho Pungpungan, 2025)
Despite the proliferation of international human rights instruments, the enforcement of these rights remains a persistent challenge in global governance. This article explores the structural, legal, and political obstacles that hinder the effective protection of human rights under international law. Drawing on a qualitative library research approach, the study examines the limitations of international courts and treaty bodies, the lack of binding enforcement mechanisms, issues of state sovereignty, and political selectivity in applying international standards. The findings suggest that although significant normative frameworks exist such as the Universal Declaration of Human Rights, the International Covenants, and regional human rights conventions their implementation is uneven and often undermined by geopolitical interests and weak institutional authority. This article contributes to ongoing debates by emphasizing the need for stronger compliance mechanisms, improved state accountability, and enhanced cooperation between international institutions and domestic legal systems. Ultimately, addressing enforcement gaps is essential for the realization of human rights as universal and justiciable standards.